2021
DOI: 10.3389/fchem.2021.734280
|View full text |Cite
|
Sign up to set email alerts
|

Direct N-Glycosylation Profiling of Urine and Prostatic Fluid Glycoproteins and Extracellular Vesicles

Abstract: Expressed prostatic secretions (EPS), also called post digital rectal exam urines, are proximal fluids of the prostate that are widely used for diagnostic and prognostic assays for prostate cancer. These fluids contain an abundant number of glycoproteins and extracellular vesicles secreted by the prostate gland, and the ability to detect changes in their N-glycans composition as a reflection of disease state represents potential new biomarker candidates. Methods to characterize these N-glycan constituents dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 42 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…To obtain maximal coverage of N -glycans from the soybean root nodules, we tested and compared commercially available recombinant PNGaseF PRIME that has been widely used in N -glycan MALDI-MSI of mammalian tissues (Powers et al, 2014 ; Carter et al, 2020 ; Blaschke et al, 2021 ; Mcdowell et al, 2021 ) and acidic PNGase H+ that has previously shown high specificity in bulk plant N -glycan profiling (Du et al, 2015 ). For assessing their efficiency, we concurrently sprayed these enzymes over the cross-section of wild type and nifH - FFPE soybean root nodule, analyzed released glycans by MALDI-MSI, and automatedly annotated N -glycans using the NGlycDB (Velickovic et al, 2021 ) in METASPACE.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain maximal coverage of N -glycans from the soybean root nodules, we tested and compared commercially available recombinant PNGaseF PRIME that has been widely used in N -glycan MALDI-MSI of mammalian tissues (Powers et al, 2014 ; Carter et al, 2020 ; Blaschke et al, 2021 ; Mcdowell et al, 2021 ) and acidic PNGase H+ that has previously shown high specificity in bulk plant N -glycan profiling (Du et al, 2015 ). For assessing their efficiency, we concurrently sprayed these enzymes over the cross-section of wild type and nifH - FFPE soybean root nodule, analyzed released glycans by MALDI-MSI, and automatedly annotated N -glycans using the NGlycDB (Velickovic et al, 2021 ) in METASPACE.…”
Section: Resultsmentioning
confidence: 99%
“…Equivalent approach based on MALDI-MS imaging (MSI) can also be used to profile N-glycome of more complex samples, e.g., urine, prostatic fluids, and expressed prostatic secretions. 196 Although this novel rapid workflow has not yet been applied on a larger sample set, the approach does not require steps of glycan labeling, derivatization, and/or purification, making it attractive for future HT clinical applications.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Alternative slide-based strategy to directly profile N -glycans from serum and plasma samples has been recently developed by Blaschke et al The approach consists of 1 up to 2 μL of serum/plasma spotting on an amine-reactive slide, delipidation, and desalting steps followed by PNGase F deglycosylation by spraying the enzyme directly on the slide and analysis with MALDI-FTICR-MS. Equivalent approach based on MALDI-MS imaging (MSI) can also be used to profile N -glycome of more complex samples, e.g., urine, prostatic fluids, and expressed prostatic secretions . Although this novel rapid workflow has not yet been applied on a larger sample set, the approach does not require steps of glycan labeling, derivatization, and/or purification, making it attractive for future HT clinical applications.…”
Section: Technologiesmentioning
confidence: 99%
“…Expressed prostatic secretions-urine samples, collected performing a gentle massage of the prostate gland during DRE prior to biopsy, prostatic fluids and urine were successfully analyzed by MALDI imaging to detect N -glycan profiles in view of new biomarkers discovery [ 40 ]. Glycoproteins were immobilized on an amine reactive slide and digested by N -glycosidase.…”
Section: Urine Samples Analysismentioning
confidence: 99%